2018
DOI: 10.4103/iju.iju_133_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficiency and complications of lumenis and wolf morcellators after holmium laser enucleation of the prostate

Abstract: Introduction:Holmium laser enucleation of the prostate (HoLEP) is a recognized option for the surgical management of benign prostatic hyperplasia. While the laser parameters and enucleation techniques have been widely studied, the morcellation techniques still remain under-evaluated. The current study evaluates the two commonly used morcellation devices for their in vivo efficiency and patient safety.Materials and Methods:A total of 222 patients who underwent HoLEP at two medical centres between January 2011 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 10 publications
(19 reference statements)
0
21
0
1
Order By: Relevance
“…All ceramic restorations are esthetically advantageous and are increasingly used for both anterior and posterior restorations. 1 Laminate veneers have many indications to improve esthetics such as discoloration, hypocalcification, peg lateral teeth, fluorosis, 2 fractured teeth and diastema. 3 The longevity of these restorations is limited by caries around the margins, discoloration, microleakage of the resin cement and marginal fracture of restorations.…”
Section: Introductionmentioning
confidence: 99%
“…All ceramic restorations are esthetically advantageous and are increasingly used for both anterior and posterior restorations. 1 Laminate veneers have many indications to improve esthetics such as discoloration, hypocalcification, peg lateral teeth, fluorosis, 2 fractured teeth and diastema. 3 The longevity of these restorations is limited by caries around the margins, discoloration, microleakage of the resin cement and marginal fracture of restorations.…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized prospective study by El Tayeb et al, the morcellation efficiency of Piranha was higher than that of VersaCut; however, the difference was not statistically significant (22). In contrast to these studies, VersaCut had a shorter morcellation time (9.8 min vs. 14.5 min) and higher morcellation efficiency than Piranha (8.4 g/ min vs. 4.7 g/min) in another study (17). In a study comparing the efficiency and reliability of DrillCut and VersaCut morcellators, there was no significant difference between their morcellation times; however, it was found that the efficiency of VersaCut morcellator was significantly higher (3.6 vs. 4.9 g/min; p= 0.03) (20).…”
Section: Discussionmentioning
confidence: 88%
“…In the morcellation step, the last step of HoLEP, free prostate tissue pushed into the bladder following enucleation is taken out in small pieces. The tissue morcellators used in this pro- cess are designed to perform suction (aspiration) and tissue cutting (8,17). The suction removes the morcellated tissues out of the bladder while keeping the tissue close to the blade, and the movable blade of the morcellator breaks the prostatic adenoma tissue into small fragments.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, effective haemostasis before morcellation and adequate bladder perfusion during morcellation to maintain bladder filling is of vital importance to prevent bladder injury during AEEP. Interestingly, Maheshwari Wagaskar and Maheshwari () explored whether morcellation devices played a role in the occurrence of complication, and eventually, they found that deep muscle or bladder mucosal impairment was significantly more common for reciprocating morcellators compared with oscillating morcellators. A small amount of flushing fluid extravasation owing to intra‐operative bladder injury is more frequent with no need of further treatment.…”
Section: Evidence Synthesismentioning
confidence: 99%